Respuesta :

9514 1404 393

Answer:

  a) y' = x^2(3x·ln(6x) +1)

  b) y' = 6e^(3x)/(1 -e^(3x))^2

Step-by-step explanation:

The applicable rules for derivatives include ...

  d(u^n)/dx = n·u^(n-1)·du/dx

  d(uv)/dx = (du/dx)v +u(dv/dx)

  d(e^u)/dx = e^u·du/dx

  d(ln(u))/dx = 1/u·du/dx

__

(a)

  [tex]y=x^3\ln{(6x)}\\\\y'=3x^2\ln{(6x)}+\dfrac{x^3\cdot6}{6x}\\\\\boxed{\dfrac{dy}{dx}=3x^3\ln{(6x)}+x^2}[/tex]

__

(b)

  [tex]y=\dfrac{1+e^{3x}}{1-e^{3x}}=1+\dfrac{2}{1-e^{3x}}=1+2(1-e^{3x})^{-1}\\\\y'=-2(1-e^{3x})^{-2} (-3e^{3x})\\\\\boxed{\dfrac{dy}{dx}=\dfrac{6e^{3x}}{(1-e^{3x})^2}}[/tex]